Habermasian Discourse Theory for Educational Policymaking: Attending to Perspective Taking and Communicative Agency - Kelly, Darron (Philosophical Inquiry in Education, 2023)
This paper identifies and considers issues of perspective taking and communicative agency in applying Jürgen Habermas’s discourse theory to policymaking in educational settings. The central question is whether Habermas provides an epistemic framework that supports reciprocal and sincere expressions of the views and interests of individuals in a heterogeneous society. Examining this question leads to a discussion of “practical discourse” in light of a willingness of participants to reach mutual understanding and agreement, and the centrality of perspective taking and communicative agency in such discourses. Also examined is a conceptualization of “application discourses,” the implications of such discourses for perspective taking and communicative agency, and the role these discourses might play in further assuring the overall inclusivity and context sensitivity of applying education policies in specific circumstances. The paper then gives a brief re-analysis of an empirical study that used Habermas’s concept of the “ideal speech situation” as a normative framework for interpreting data. The re-analysis means to illustrate the practical value of practical discourse for guiding and assessing educational policymaking. The paper ends with a short justification of the necessity of attending to perspective taking and communicative agency when viewing education as a basic human right.